Pengendalian Stok Ikan Berbasis Website Menggunakan Metode EOQ dan JIT di PT. Agung Sumatera Samudera Abadi (ASSA) Sibolga - Yolanda Sianturi; Triase Triase; Fathiya Hasyifah Sibarani (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The company PT. Agung Sumatera Samudera Abadi (ASSA) Sibolga sales system still uses a manual system using notebooks. So that it can slow down the way employees work and become ineffective. limitations in monitoring and controlling stock in real-time and fish stock supplies also often occur shortages or excesses which can result in losses. The shortage of fish stock is caused by the frequency of fish demand being greater than the stock provided. While the excess fish stock is caused by the frequency of fish demand being less than the stock provided. so using the Economic Order Quantity (EOQ) and Just In Time (JIT) methods which are used to optimize and minimize inventory and manage fish stock at PT.ASSA by reducing excess inventory and shortages, and facilitating the inventory control process in real-time. The results of this study are in the form of a computerized system used to determine fish inventory using the EOQ and JIT methods. From the calculation results of the two methods, the final results of the EOQ method were obtained with a message frequency of 14 times a month with a quantity of fish messages of 4,565,650 Kg, while the JIT method was obtained with a message frequency of 6 times a month with a quantity of 2,262,548 Kg and with a reserve stock of 1,866,602 Kg.